Supervisi Akademik Pengawas Sekolah Berbasis Rapor Pendidikan dalam Penguatan Kualitas Proses Pembelajaran Tinjauan Literatur dan Kesenjangan Penelitian - Dinita, Daniar Rahmah; Joko Raharjo, Tri; Sumartiningsih, Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Academic supervision conducted by school supervisors is fundamentally intended to improve the quality of learning and teacher professionalism; however, in practice, it is still dominated by administrative and evaluative approaches, making it less optimal as a professional learning mechanism. This study aims to examine the implementation of Education Report-based academic supervision in strengthening the quality of the learning process in primary schools, identify existing research gaps, and formulate directions for more effective supervision development. The study employs a qualitative approach using a literature review method combined with gap analysis of various national and international studies. The findings indicate that academic supervision has significant potential to enhance learning quality when implemented systematically, collaboratively, and reflectively; however, a gap remains between its ideal conceptual framework and its practical implementation. Furthermore, the integration of data in supervision practices is still limited due to low data literacy and insufficient institutional support. Therefore, a transformative data-driven academic supervision model is needed, integrating teacher professional development, pedagogical reflection, and evidence-based decision making grounded in the Education Report.